1997
DOI: 10.1007/s002849900216
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic Gram-Positive and Gram-Negative Bacteria Exhibit Differential Sensitivity to and Transformation of 2,4,6-Trinitrotoluene (TNT)

Abstract: A systematic evaluation of the ability of different bacterial genera to transform 2,4,6-trinitrotoluene (TNT), and grow in its presence, was conducted. Aerobic Gram-negative organisms degraded TNT and evidenced net consumption of reduced metabolites when cultured in molasses medium. Some Gram-negative isolates transformed all the initial TNT to undetectable metabolites, with no adsorption of TNT or metabolites to cells. Growth and TNT transformation capacity of Gram-positive bacteria both exhibited 50% reducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
43
0
1

Year Published

1998
1998
2005
2005

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(52 citation statements)
references
References 24 publications
8
43
0
1
Order By: Relevance
“…These chemicals have multiple applications in the synthesis of polyurethane foams, herbicides, insecticides, pharmaceuticals, and explosives (99), all of which are more recalcitrant than the raw material from which they are synthesized. Comprenhensive reviews of catabolic pathways leading to the degradation of nitroaromatic compounds are available (27,53,54,79,87,88,106,122,123,141,147,170,(210)(211)(212)243).…”
Section: Introductionmentioning
confidence: 99%
“…These chemicals have multiple applications in the synthesis of polyurethane foams, herbicides, insecticides, pharmaceuticals, and explosives (99), all of which are more recalcitrant than the raw material from which they are synthesized. Comprenhensive reviews of catabolic pathways leading to the degradation of nitroaromatic compounds are available (27,53,54,79,87,88,106,122,123,141,147,170,(210)(211)(212)243).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, some Grampositive bacteria, such as members of the genera Corynebacterium, Rhodococcus and Streptomyces, are able to mineralize a wide array of aromatic compounds 2,13,15,19,20,28,34) . Comparative studies indicated that there are extensive differences between the biodegradation processes in Grampositive and Gram-negative bacteria 3,9,12,14,16,19,25,27) . However, our understanding of the aromatic degradation in Grampositive bacteria at the genetic and biochemical levels is relatively limited.…”
mentioning
confidence: 99%
“…Several Corynebacterium species isolated from soil are able to degrade styrenes 20) , 2,4-dichlorobenzoate 28) , 2,4,6-trinitrotoluene 14) or other aromatic compounds 5,7,10,34) . Our previous studies demonstrated that C. glutamicum could use different aromatic compounds as a sole source of carbon and energy and, multiple ring cleavage pathways might occur in this bacterium [31][32][33] .…”
mentioning
confidence: 99%
“…Growth experiments revealed that strain JS71 used 3 mol of nitrogen per mol of CL-20. 4,6,8,10,4,6,8,10,) is a new, highly energetic explosive related to the explosives RDX (hexahydro-1,3,5-trinitro-1,3,5-triazine) and HMX (octahydro-1,3,5,7-tetranitro-1,3,5,7-tetrazocine) (Fig. 1).…”
mentioning
confidence: 99%